أثر سلوك التكاليف على ربحية الشركات دراسة تطبیقیة في شركة ئاال النتاج المشروبات الغازية والمياه الصحية المحدودة في محافظة السلیمانیة - عزيز, هێمن محمد (Sulaimani Journal for Humanities, 2022)
the conducted subject in this study is the cost behaviour in industrial companies in Kurdistan region. This is through the comparison of the performance of Ala Company (for Sparkle drink production) in two season winter and summer. This is due to the demand increment on the company’s production in summer and revealing the pattern that may affect the ratio of net profit of the company, in which that the manager has the substitutional choice and freedom between fixed and variable cost in cost time period. This will lead to the company’s profit maximization as one of the factors of competitive advantage. The aim of this study is to test and evaluate cost behaviour in industrial companies which is considered as one of the most important factors that has the role of providing efficient and necessary information for planning, monitoring, decision making, and proffer administrative, accounting, and economical tools to help the industrial companies in Kurdistan region in the aim of reducing the cost of a unit as one of the competitive advantage factors and its important in profit maximization. This study concludes that the best cost structural in winter is to have high variable costs and the fixed cost has to be in its minimal level and vice versa for summer. At the end most vital recommendation has been introduced in the aim of improving the test and evaluation process for cost structure, which is considered to be one of the most important factors in industrial companies that will help in providing efficient data and information for planning, monitoring, and decision making.
Keywords: Cost behaviour; Fixed cost; Variable cost; profit maximization